2015
DOI: 10.14295/2238-6416.v70i2.400
|View full text |Cite
|
Sign up to set email alerts
|

DESENVOLVIMENTO E CARACTERIZAÇÃO DE DIFERENTES FORMULAÇÕES DE SORVETES ENRIQUECIDOS COM FARINHA DA CASCA DA JABUTICABA (Myrciaria cauliflora)

Abstract: O objetivo foi realizar a caracterização físico-química da farinha da casca de jabuticaba, bem como desenvolver três formulações de sorvetes (enriquecidos com 0, 5 e 10% desta farinha) e avaliar as características físico-químicas e sensoriais dos mesmos. Os frutos foram despolpados, as cascas desidratadas, trituradas e peneiradas para obtenção da farinha que foi analisada quanto aos teores físico-químicos. Em seguida, foram desenvolvidas três formulações de sorvetes (com 0%, 5% e 10% de FCJ) e, verificadas as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
2
0
13
Order By: Relevance
“…This effect was verified in the present work, since the fibre is hygroscopic, promoting greater water retention in the products (WALKER et al, 2014). In addition, the high citric acid (9.4 g.100 g -1 ) (LAMOUNIER et al, 2015) and phenolic compound (556.3 g GAE.kg -1 ) (LEITE-LEGATTI et al, 2012) contents found in the JSF result in the product acquiring acid and adstringent flavours, respectively (LESSCHAEVE; NOBLE, 2005). These characteritics could be responsible for the reduction in the scores for flavour of the muffins containing higher JSF levels.…”
Section: Palavrassupporting
confidence: 83%
“…This effect was verified in the present work, since the fibre is hygroscopic, promoting greater water retention in the products (WALKER et al, 2014). In addition, the high citric acid (9.4 g.100 g -1 ) (LAMOUNIER et al, 2015) and phenolic compound (556.3 g GAE.kg -1 ) (LEITE-LEGATTI et al, 2012) contents found in the JSF result in the product acquiring acid and adstringent flavours, respectively (LESSCHAEVE; NOBLE, 2005). These characteritics could be responsible for the reduction in the scores for flavour of the muffins containing higher JSF levels.…”
Section: Palavrassupporting
confidence: 83%
“…Em polpa de jabuticaba analisada por Becker et al (2015), foi verificado valor de 8,0 °Brix, inferior ao da polpa de jabuticaba do presente estudo. Frutas com maiores valores de SST favorecem a adição de menor quantidade de açúcar ao produto para atingir a concentração final (Lamounier et al, 2015).…”
Section: Caracterização Física E Físico-química Das Polpas E Blendsunclassified
“…The results obtained for pH and TTA of guabijú lyophilized from both harvests (Table 1) characterize it with a low acid product. Lamounier et al (2015) produced a flour from jabuticaba peel and obtained a pH of 3.27 and TTA of 9.4 g citric acid × 100 g -1 , which presented a greater acidity compared to GLPD and GLPJ. The authors also obtained higher ash (4.23 g × 100 g -1 ) and moisture (16.13 g × 100 g -1 ) contents compared to guabijú lyophilized.…”
Section: Resultsmentioning
confidence: 99%